PENGARUH KOMITMEN ORGANISASI, EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL, KEADILAN ORGANISASI, BUDAYA ETIS ORGANISASI, DAN PENEGAKAN HUKUM TERHADAP KECENDERUNGAN KECURANGAN - Riko Adi Saputro (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to analyze the effect of organization commitment, internal control system effectiveness, organizational justice, organization ethical culture organization, and law enforcement on fraud tendencies. The research is carried out in a number of offices of Mojokerto using a questionnaire. Researchers obtain 71 people who work in the financial office of Mojokerto as the respondents. Data analysis method used in this study is the multiple linear regression analysis using SPSS. The results show that partially organizational commitment, the effectiveness of internal control systems, organizational justice, and the rule of law negatively affect the tendency of cheating, while the ethical culture of the organization has no effect on the tendency of fraud. The implication of this research for the organization is that the government sector organizations have to pay attention to the factors that may cause the propensity of fraud.Keywords: organization commitment, internal control system effectiveness, ethical culture, organizational fairness, law enforcement, fraud tendency